Aktivitas antibakteri asap cair dan daya awetnya terhadap bakso ikan - Ita Zuraida; Rokhani Hasbullah; . Sukarno; Slamet Budijanto; Sulusi Prabawati; . Setiadjit (Jurnal Ilmu Pertanian Indonesia, 2009)
The study were investigated antibacterial activity of liquid smoke from coconut shell and its applications of fishball at room temperature (27-28°C) and refrigeration temperature {4±1°C). The Minimum Inhibitory Concentration (MIC) of liquid smokel against Pseudomonas aeruginosa and Staphylococcus aureus were determined using broth or agar dilution methods. liquid smoke showed bactericidal effects with P. aeruginosa than S. aureus. MIC of liquid smoke was 0.40°/o against S. aureus and 0.22°/o against P. aeruginosa. Trial in fishball, showed that boiling in 2.5% liquid smoke and storage at 27-28°C and 4±1°C were inhibited the growthof total bacteria and increased shelflife 16 hours and 8 days than no treatment (based on SNI 01-3819-1995), respectively, and retarded the increased in pH and moisture content after storage. The results indicated thatliquid smoke was an effective inhibitor of fishball spoilage.